An in vitro evaluation of canal transportation and centering ability of ProTaper Universal, Hyflex EDM, and WaveOne gold using microcomputed tomography - Ashwin Ravichandran; Veni Ashok Baskaran; Shankar Narayanan Gopal; Venkatesan S Motilal; Meenakshisundram Rajasekaran; Anil Kumar Ramachandran (Wolters Kluwer Medknow Publications, 2022)
Aim: The study was to determine and compare the values of canal transportation and centering ability of ProTaper Universal (PTU), Hyflex EDM (HEDM), and WaveOne GOLD (WOG) using microcomputed tomography (Micro-CT). Methods: Sixty mandibular molar mesiobuccal canals were randomly allocated into three groups, each with 20 samples: PTU (group one), HEDM (group two), and WOG (group three). Micro-CT was used to scan samples before and after instrumentation. Three-dimensional scans of root cross-sections at 3 mm, 6 mm, and 9 mm from the apex were obtained to measure canal transportation and centering ability. For statistical analysis, SPSS software was utilized. P = 0.05 was used as the significance level. Results: When compared all three systems, PTU files had the highest transportation and were less centered. HEDM and WOG showed no significant difference (P > 0.05). Conclusion: Curved roots canals were shaped without any significant canal transportation by Hyflex EDM and WOG when compared with PTU files.